Detecting temperature breaks in the initial stages of the citrus export cold chain: A case study - Christoff A. Conradie; Leila L. Goedhals-Gerber; Frances E. van Dyk (Journal of Transport and Supply Chain Management, 2022)
Background: Fruit is an important export commodity for South Africa and accounts for 35% of its agricultural exports. South Africa is the second largest citrus exporter in the world, behind Spain. Maintaining the postharvest cold chain is key to ensuring that fruit quality meets export standards.